Cost assessment for implementing an oral health team in the Family Health Strategy in the state of Minas Gerais (Research, Society and Development, 2022)
Health care costs, including oral health care, are relevant and tend to increase, while funding sources are limited. In Brazil, economic assessments in health, especially in the area of oral health, are still incipient and little incorporated into management practices. The aim of this study was to calculate the investment needed to implement an Oral Health Teams (OHT) in the state of Minas Gerais. The methodology consisted of an economic evaluation of an OHT implementation cost analysis type. The calculation of investments was obtained by adding the costs of human resources, equipment, furniture, instruments and maintenance of dental equipment, which are the direct costs. Recurring costs were those spent on electricity, water and telephone. The total investment cost for implementing an OHT  in the state of Minas Gerais was estimated at BRL 67.329.02 for MOD I, consisting of DS and OHA, and BRL 67.467.26 for MOD I, consisting of DS and OCT. In MOD II, the implementation cost was R$85.842.46 for the team consisting of DS, OCH and OHA and R$85.980.70 for the team consisting of DS and two OCH. The study showed that municipalities are primarily responsible for funding oral health actions and services in primary care. It is necessary that the federal and state spheres, particularly in Minas Gerais, participate more effectively in the implementation of the OHT.